„Jakaś groza wieje od tych pól ponurych” – świadkowie i dziedzictwo masowych, drugowojennych zbrodni w Dolinie Śmierci w Chojnicach - Kobiałka, Dawid (Folia Praehistorica Posnaniensia, 2021)
This paper discusses the results of the research carried out in a project entitled An archaeology of the Death Valley. First, the historical context related to mass killings on the outskirts of Chojnice during the Second World War is sketched. Then, the results of the archaeological field research are presented. The last part is about ethnographic research which allowed to document various memories related to mass killings in the Death Valley as well as human and non-human witnesses of these events. The idea behind this paper is to show that archaeology and ethnography are crucial in discovering and documenting sites of mass killings and their heritage.